Concept of construction of the electrical complex for monitoring and regulation of the biogas reactor operation mode - Zablodskyi, M.; Babak, D. (Energy and Automation, 2026)
This article focuses on improving the operational efficiency of existing biogas plants through the implementation of an electrical system based on a submersible multifunctional electromechanical converter (PEMC). The aim of the study is to develop a concept for a system to monitor and regulate the operating mode of a biogas reactor. The system combines active thermomechanical and electromagnetic effects on the substrate with distributed intelligent monitoring. The system’s architecture is based on the synergistic interaction of two functional subsystems: the PEMP—an actuator located directly within the reactor’s working volume that provides simultaneous mixing, heating, and magnetization of the substrate, spatial temperature monitoring, rotation speed control, and, if necessary, the intensity of the magnetic field in the external rotor array; a device for automatic parameter control—a measurement module that provides periodic, high-precision monitoring of physicochemical parameters (pH, Redox, density, O2, NH3, H2 content, etc.) with an automatic maintenance function (cleaning and calibration) for the sensors. This allows for the transition to comprehensive fermentation control, where thermal and mechanical flows are formed adaptively to the state of the medium. To evaluate the dynamic properties of the rotary transformer, a series of measurements was conducted on an experimental sample while varying the frequency of the input P-wave signal. It was found that the most balanced parameters were observed at 2 kHz: sufficient induced voltage and moderate short-circuit current. Future development prospects include linking the assessment of the methanogenesis process not only to the influence on the substrate through changes in operating parameters inside the bioreactor, but also to the conditions affecting the pretreatment of raw materials (primarily lignin-containing ones). Recieved 2025-12-01 Recieved 2026-01-21 Accepted 2026-02-11